2022
DOI: 10.1016/j.ymthe.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel genome-editing-based approaches to treat motor neuron diseases: Promises and challenges

Abstract: Motor neuron diseases are untreatable with common pharmacological approaches. Spinal muscular atrophy (SMA) is caused by SMN1 gene mutations leading to lowered SMN expression. Symptoms are alleviated in infants with a higher copy number of the SMN2 gene, which, however, displays a splicing defect resulting in low SMN levels. Amyotrophic lateral sclerosis (ALS) is caused by a number of mutations, with C9orf72 repeat expansions the most common genetic cause and SOD1 gain-of-function mutations the first genetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…In recent years, advances in the understanding of the molecular basis of C9orf72-related clinical phenotypes and the development of disease models have led to the identification of innovant disease modifying drugs [11,15,16]. Although currently available C9orf72 animal models lack some of the key features of the disease, such as reduced survival and neuromuscular decline [17,18], they can recapitulate the molecular signature of the disease and were used for therapeutic pre-clinical development [19,20].…”
Section: Innovative Therapies For C9orf72-als: From Pre-clinical Deve...mentioning
confidence: 99%
“…In recent years, advances in the understanding of the molecular basis of C9orf72-related clinical phenotypes and the development of disease models have led to the identification of innovant disease modifying drugs [11,15,16]. Although currently available C9orf72 animal models lack some of the key features of the disease, such as reduced survival and neuromuscular decline [17,18], they can recapitulate the molecular signature of the disease and were used for therapeutic pre-clinical development [19,20].…”
Section: Innovative Therapies For C9orf72-als: From Pre-clinical Deve...mentioning
confidence: 99%
“…Previous studies have shown that single point mutations on the SMN2 gene can lead to an increase in SMN expression. However, until now, it has not been shown with the CRISPR system whether these mutations can be created synthetically in the laboratory and have the capacity to increase the production of SMN protein (Miccio et al, 2022). We designed a proof-of-concept experiment for the first time with this study by performing pegRNA designs that can create these point mutations, and we used the Jurkat cell line with low SMN expression for this.…”
Section: Discussionmentioning
confidence: 99%
“…Genome editing techniques enable direct, simple, and efficient repair and correction of abnormal genes, and are expected to enable treatments that were not possible with conventional gene therapy. Although many barriers, such as off‐target activity, delivery systems, and immunogenicity, must be overcome, the therapeutic application to single‐gene diseases, such as familial ALS, is promising 73 . A phase I study in patients with hereditary TTR amyloidosis has already started (http://clinicaltrials.gov Identifier: NCT04601051).…”
Section: Discussionmentioning
confidence: 99%